THALASSAEMIA INTERMEDIA : AN UPDATE - Maria Domenica Cappellini; Khaled M. Musallam; Ali Taher (Mediterranean Journal of Hematology and Infectious Diseases)
Our understanding of the molecular and pathophysiological mechanisms underlying the disease process in patients with thalassaemia intermedia (TI) has substantially increased over the past decade. TI encompasses a wide clinical spectrum of beta-thalassaemia phenotypes. Some TI patients are asymptomatic until adult life, whereas others are symptomatic from as young as 2 years of age. A number of clinical complications commonly associated with TI are rarely seen in thalassaemia major, including extramedullary hematopoiesis, leg ulcers, gallstones, thrombosis and pulmonary hypertension. There are a number of options currently available for managing patients with TI, including transfusion therapy, iron chelation therapy, modulation of foetal haemoglobin production and haematopoietic stem cell transplantation. However, at present, there are no clear guidelines for an orchestrated optimal treatment plan.